Economic Contribution of Regional Feeder Ports to The Local Economy In Indonesia - Ibnu Syabri; Pritta Andrani Widyanarko (TEKNIK, 2017)
Indonesia regional feeder ports’ main function is to serve marine transport activities between regency/city in a province in limited quantities. The intention of the government to make marine transportation as the backbone of national logistic transportation system puts these ports to an important position, as suppliers for the main and/or collector ports and as goods distribution centers for the region from the bigger ports. Not only as a provider of accessibility between regions, regional feeder ports should be seen as an investation to boost regional economy. This study aims to explain the influences of regional feeder ports on regency/city economy, based on the port types: (1) cargo ports, and (2) cargo & passengers ports. Results showed that both types of ports have positive influences on the regency/city economy, although it is not related to region’s economic base sector. Cargo ports which are mainly located on west area of Indonesia, supports the region’s economy more than cargo & passenger ports which are mainly located on the east.